ATENUASI INTERNAL MULTIPLE MENGGUNAKAN METODE INTERNAL MULTIPLE ELIMINATION - Azizah Rakhmawati, Ladaya
Multiples are one of the noises on marine seismic data record that reflected more than once at the surface or the subsurface before arriving at the receivers in the surface. The most challenging multiple to attenuate is internal multiples. Compared to surface multiples, internal multiples are more difficult to remove due to the similarity of the characters with primaries. Resulting resistance to the traditional methods. Internal multiples are events that reflect at least once at the subsurface and do not have a relation with the surface. These multiples occur when there is a low-velocity layer that interbedded with high-velocity layers. In this research, internal multiples are decreased using an internal multiple elimination method. This method has a concept that predicts multiples and subtracts adaptively with raw seismic data. Then, the concept is applied to the synthetic data and also to the field data to see the effectivity for reducing internal multiples. The result from data processing of seismic synthetic model and field data from Offshore Northwest Java Basin (ONWJ) showed that this procedure could attenuate internal multiples.